2011
DOI: 10.1093/aob/mcq269
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of embryogenic callus in Medicago truncatula: the fate of the pluripotent and totipotent stem cells

Abstract: The ontogeny of embryogenic callus in M. truncatula relates to explant orientation and is driven by the dynamics of pluripotent procambial cells, which proliferate and differentiate into vasculature. The ontogeny is also related to de-differentiated mesophyll cells that acquire totipotency and form the majority of embryos. This contrasts with other species where totipotent embryo-forming initials mostly originate from procambial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 56 publications
1
38
0
1
Order By: Relevance
“…A study by Rose et al [23] on the origin of roots in leaf cultures of Medicago truncatula, showed that vein procambial cells stimulated by auxin gave rise to callus cells that ultimately generated root meristems. Further studies on regeneration in M. truncatula also revealed that somatic embryos in leaf cultures originated from procambial cells or dedifferentiated mesophyll cells that become totipotent [24]. Cell proliferation within the bundle sheath was also observed in leaf explants of H. occidentalis [25], leading to rhizogenesis.…”
Section: Discussionmentioning
confidence: 95%
“…A study by Rose et al [23] on the origin of roots in leaf cultures of Medicago truncatula, showed that vein procambial cells stimulated by auxin gave rise to callus cells that ultimately generated root meristems. Further studies on regeneration in M. truncatula also revealed that somatic embryos in leaf cultures originated from procambial cells or dedifferentiated mesophyll cells that become totipotent [24]. Cell proliferation within the bundle sheath was also observed in leaf explants of H. occidentalis [25], leading to rhizogenesis.…”
Section: Discussionmentioning
confidence: 95%
“…4D). Likewise, calli that give rise to somatic embryos have a cellular origin clearly distinct from pericycle or vascular cells in Medicago truncatula (Wang et al, 2011). It was reported that epidermal cell fate in developing leaves of Arabidopsis thaliana (Arabidopsis) can also be overwritten by overexpression of the RWP-RK protein RKD4 in order to initiate embryogenesis (Waki et al, 2011) (Fig.…”
Section: Cellular Origins Of Regenerationmentioning
confidence: 99%
“…bras., Brasília, v.46, n.8, p.814-821, ago. 2011 citocininas e auxinas (Wang et al, 2011). Estas últimas mostraram padrões estabelecidos quanto à polaridade de transporte, o que influencia a formação dos novos embriões.…”
Section: Figura 1 Distribuição Temporal De Frequência Da Germinação unclassified